2020
DOI: 10.1001/jamanetworkopen.2019.17577
|View full text |Cite
|
Sign up to set email alerts
|

Association of Repeated Antibiotic Exposure Up to Age 4 Years With Body Mass at Age 4.5 Years

Abstract: IMPORTANCE Antibiotic exposures in early life may affect weight by altering gut microbiota, potentially increasing the likelihood of childhood obesity. OBJECTIVE To examine whether repeated antibiotic exposure by age 48 months is associated with higher body mass index (BMI) at age 54 months. DESIGN, SETTING, AND PARTICIPANTS This research was undertaken within a prospective cohort study in New Zealand (Growing Up in New Zealand) that recruited 6853 children antenatally during 2009 to 2010. At the 54-month foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 23 publications
0
36
1
2
Order By: Relevance
“…In sharp contrast to previous studies, only two studies have reported no difference between exposure to antibiotics and childhood overweight/obesity [ 112 , 118 , 119 ]. However, in the first study, only a single class of antibiotics was prescribed as prophylaxis; therefore, the results might have been affected by the type and dosage of the administered antibiotic, while in the second study, infection per se rather than the administration of antibiotics accounted for the observed increased body weight.…”
Section: Administration Of Antibiotics As a Cause Of Obesitycontrasting
confidence: 70%
See 1 more Smart Citation
“…In sharp contrast to previous studies, only two studies have reported no difference between exposure to antibiotics and childhood overweight/obesity [ 112 , 118 , 119 ]. However, in the first study, only a single class of antibiotics was prescribed as prophylaxis; therefore, the results might have been affected by the type and dosage of the administered antibiotic, while in the second study, infection per se rather than the administration of antibiotics accounted for the observed increased body weight.…”
Section: Administration Of Antibiotics As a Cause Of Obesitycontrasting
confidence: 70%
“… ✓ Increased number of antibiotic classes, longer duration of antibiotic administration and earlier antibiotics administration (before 24 months of age) was related to childhood obesity at 30–36 months of age. Chelimo et al 2020[ 118 ] 6,853 children aged 54 months, New Zealand I) Antibiotics administration during 48 months of age ✓ Administration of antibiotics for ≥ 9 times was related to an increased likelihood of obesity, when compared with no exposure (adjusted odds ratio, 2.41; 95% CI, 1.07–5.41). Children whose exposure began in the 1 year of life had a higher adjusted mean (SD) BMI-for-age z score than those not exposed (1.06 [0.05] vs 0.89 [0.09]; P = .03), ✓ Repeated antibiotics administration in early childhood was related to a higher mean BMI-for-age z score and an increased likelihood of obesity.…”
Section: Administration Of Antibiotics As a Cause Of Obesitymentioning
confidence: 99%
“…The main limitation of this study is that potentially important covariates associated with the development of childhood obesity may have not been included in the final multivariate models and, thus, the magnitude of the association between the IFI and obesity may be overestimated. Examples of covariates include objective infant PA and sleep measures which were not measured in the preschool years in this cohort, mode of delivery and antibiotic use, both recently reported as associated with child body size in this cohort (53,54) . The exclusion of children born with low-birth weight and preterm aimed to accounr for children more likely to have medical and developmental issues that may impcat feeding and growth.…”
Section: Study Findings In Relation To Other Studiesmentioning
confidence: 99%
“…However, this process is vulnerable and can be disturbed by various pre‐, intra‐, and post‐partum factors, including delivery and feeding modes, antibiotics, maternal overweight and diet, and gestational diabetes 131 . Interestingly, all these factors are linked to increased susceptibility to adolescent and (or) adult obesity 132–137 . A large‐scale longitudinal birth cohort study indicated that early‐life infection, rather than antibiotic administration, is associated with late‐life obesity, 138 which indicates that inflammatory responses, as seen during early‐life gut dysbiosis, increases the susceptibility to obesity.…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 99%
“…131 Interestingly, all these factors are linked to increased susceptibility to adolescent and (or) adult obesity. [132][133][134][135][136][137] A large-scale longitudinal birth cohort study indicated that early-life infection, rather than antibiotic administration, is associated with late-life obesity, 138 which indicates that inflammatory responses, as seen during early-life gut dysbiosis, increases the susceptibility to obesity.…”
Section: Correlations Between Serum Iga and Metsmentioning
confidence: 99%